Does the sequence of land reform and political reform matter? Evidence from state-building in Afghanistan. Issue 2 (3rd March 2016) - Murtazashvili, Ilia; Murtazashvili, Jennifer
Abstract: Property insecurity is associated with terrorism, insurgency and economic underdevelopment. For this reason, land reform is often implemented alongside political reform in post-conflict settings. In contrast, this article argues that political reform should be sequenced prior to land reform during state-building. Evidence from Afghanistan shows how land redistribution, legal titling, decentralisation of state-owned land and provision of legal services to resolve land disputes are unlikely to alleviate political violence or facilitate economic development without establishing or substantially improving political capacity, political constraints and inclusive political institutions at the local level. These findings suggest the importance of sequence in the process of land reform and political reform. More generally, political reform is a prerequisite for land reform to reduce violence and improve development prospects in post-conflict settings.